Феминный аспект сказок цикла «Умная дочь крестьянина» - Меликян, Гоар (ՀՀ ԳԱԱ Հնագիտության և ազգագրության ինստիտուտ)
Статья рассматривает вопрос феминности – женственности в народных сказках. Испокон веков женщины посвящали сказки концепту их самовыражения, укреплению их роли и места в обществе. И даже в сказках, пересказанных мужчинами, все еще можно услышать женские голоса. В статье анализируется группа сказок с активными героинями на примере сказок цикла «Умная дочь крестьянина», тип № 875 по классификации Аарне-Томпсон-Утера. Героини этого цикла сказок способны принимать самые важные решения, постоять за себя и за своих близких, дать ответы на вопросы и загадки, на которые затруднялись ответить мужчины. Героини в этих сказках не только красивы, добры, но также находчивы, умны и храбры. Они не воюют с обществом, а просто используют свой ум и интеллект, чтобы добиться желаемого. Посредством интерпретации формульных загадок и аллегорий героиня раскрывает себя, выражает свои мысли, эмоции и нравственные ценности. В этом цикле сказок на первый план выдвигаются отношения женщины и мужчины в виде семантических бинарных оппозиций. В армянском корпусе находим 22 варианта сказок данного цикла, собранных из разных регионов Армении. Эти сюжеты мы сводим к чисто женским сказкам, где женщины манипулируют речью, проявляют смекалку для утверждения своих позиций и завоевания лучшего положения. Հոդվածում արծածվում են հայ ժողովրդական հեքիաթներում առկա պատկերացումները՝ հերոսուհիների ողջախոհության, հնարամտության ու կանացի հմայքի մասին: Հնագույն ժամանակներից սկսած՝ կանանց պատմած հեքիաթները միտված են եղել կնոջ ինքնահաստատմանը, հասարակության մեջ նրա դերի և դիրքի ամրապնդմանը: Հատկանշական է, որ անգամ տղամարդ ասացողների վերապատումներում տեսանելի է կանանց դերի արժևորումը: «Գյուղացու խելացի աղջիկը» հեքիաթի օրինակով վերլուծվում է գործունյա հերոսուհիներ ունեցող մի հեքաթախումբ, որի՝ Հայասատանի պատմազգագրական տարբեր շրջաններից գրառված 22 տարբերակները միջազգային նշացանկի 875 թվահամարին: Այս հեքիաթախմբի հերոսուհիները ինքնաբավ են, ընդունակ են իրենց կայացրած որոշումներով պաշտպանելու թե՛ իրենց և թե՛ իրենց հարազատներին, լուծելու հանելուկներ, որոնց պատասխանները հաճախ տղամարդկանց չի հաջողվում գտնել: The article discusses the issue of femininity in folktales. It is well known that women play an important role in the context of folktales. They have devoted folktales they tell to the concept of their self-expression, to strengthening their role and place in society. Even in folktales retold by men, women՚s voices still can be heard. Nowadays there is a tendency to criticize classical fairytales for the passive role of heroines in them. Wе consider it to be an issue of unawareness of existence of tales with active heroines. The article analyses ՙՙThe Clever Farmgirl՚՚ cycle of folktales (Tale Type N 875 according to Aarne-Thompson-Uther՚s classification of folktales) with an active heroine. Heroines in these tales are capable of making the most important decisions, standing for themselves and for their families, finding answers to riddles and questions that men could not find answers to. Heroines in these tales are not only beautiful and kind but also inventive, intelligent and brave. They are not at war with society; they are just using their wits and intelligence to get what they desire. By interpreting allegories and solving riddles they reveal themselves, express their thoughts, emotions as well as moral values. Tales with active heroines mostly represent utopian ideas. A situation when a woman could choose a partner for her and when marriage meant love, equality and respect was considered utopian. Active heroines intend to create their own life and to change the rules of the game. In the mentioned cycle the relations between women and men in the form of semantically binary oppositions come to the fore. In Armenian corpus of folktales there are 22 variants of tales indexed as ՙՙThe Peasant՚s Wise Daughter՚՚ collected from different ethnographic regions of Armenia. Almost in all of them the plot is the same with some variations. Girls interpret allegories and formula riddles which meant family life and marriage. According to our research, these tales are feminine in their nature, where women manipulate with the help of their speech and wit in order to win a better position
Keywords: Текстологические исследования